PENGARUH SISTEM PENGENDALIAN INTERNAL, BUDAYA ETIS ORGANISASI, PENERAPAN GOOD CORPORATE GOVERNANCE DAN PERSONAL ATTITUDE TERHADAP KECENDERUNGAN FRAUD (PADA PEMERINTAH KOTA SURABAYA) - Fadel Muhamad; Susilowati, Endah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This research aims to determine the influence of the Internal Control System, Organizational Ethical Culture, Implementation of Good Corporate Governance and Personal Attitude on Fraud Tendencies. This research uses a quantitative approach and this type of research tends to be deductive. The sample population in this research is employees in the budget and finance sector at BPKAD Surabaya City. The type of data used in this research uses primary data which comes from respondents' answers obtained from questionnaires distributed to 52 respondents. The data analysis technique used in this research uses Patial Least Square (PLS) with the help of WarpPLS 7.0 software. The research results show that the Internal Control System, Ethical Organizational Culture, Implementation of Good Corporate Governance and Personal Attitude influence Fraud Tendencies.